A scoping review of seismic risk communication in Europe - Musacchio, Gemma; Saraò, Angela; Falsaperla, Susanna; Scolobig, Anna (Frontiers in Earth Science, 2023)
Although earthquakes are a threat in many countries and considerable resources have been invested in safety regulations, communities at risk often lack awareness and preparedness. Risk communication is a key tool for building resilient communities, raising awareness, and increasing preparedness. Over the past two decades, seismic risk communication has evolved significantly. This has led to a reorientation from a predominantly “one-way”, top-down communication model to the promotion of new models in which people, their needs, and their participation in disaster risk management are central elements. The 2015-2030 Sendai Framework recommendations, recent disaster experiences, and research have highlighted that new models can improve communication effectiveness. In this paper, we critically explore this transition by conducting a scoping review (n=109 publications) of seismic risk communication in Europe. We analyze the approaches, messages, tools, and channels used for seismic risk communication and how they have changed over time. The results reveal that the stated goals of seismic risk communication are, in decreasing order, to share information, raise awareness, change behaviors/beliefs, and increase preparedness. Pupils, students, and citizens are the primary recipients of communication activities. Over the years, two trends have emerged. First, “two-way”, transdisciplinary, and bottom-up communication models prevailed over the “one-way” model. Second, communication aimed more at promoting proactive behaviors than just informing the public. Face-to-face, hands-on activities, and serious games are key tools to engage with the public. The results also reveal the emerging role of social media to target different audiences/social groups. Strikingly, only one-fifth of the analyzed publications explicitly build on or tests risk communication theories. Future research could focus on comparing practices across countries and risks (e.g., earthquakes and floods) and on innovating communication theories and methodologies, especially by incorporating the role of information technologies and social media.